Riba (interest): one substance, different forms in the Nigerian economy (2019)
Many economic activities in Nigeria cloak the real identity of riba (interest) which comes in different forms; and this puts Muslims in dilemma. This paper, therefore, examines contemporary practices of riba in the Nigerian economy in the light of the Quran and the Hadith. The study reveals that some of the services rendered by the services sectors and financial services such as airtime and cheque leaves are Shari'ah compliant based on the principle of the shari‘ah maxim, Ual-kharaju bid-damarT meaning profit goes with responsibility. However, interest-based government aids and products of the services sector and financial system laden with interest are also not shari‘ah compliant based on the injunction of the Qur'an on the prohibition of interest (Q2: 275-279).